2005
DOI: 10.1116/1.1927103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxy of InAlN∕GaN heterostructures for high electron mobility transistors

Abstract: Articles you may be interested inGrowth and characterization of AlGaN/GaN/AlGaN double-heterojunction high-electron-mobility transistors on 100-mm Si(111) using ammonia-molecular beam epitaxy Suppression of surface segregation of silicon dopants during molecular beam epitaxy of ( 411 ) A In 0.75 Ga 0.25 As ∕ In 0.52 Al 0.48 As pseudomorphic high electron mobility transistor structures High mobility AlGaN/GaN heterostructures grown by plasma-assisted molecular beam epitaxy on semi-insulating GaN templates prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…On the other hand, InN can only be grown at low temperatures and high ammonia partial pressures, whereby high ammonia partial pressures have also a strong effect on the AlN growth rate. However, these problems have been widely overcome in first promising experiments [8][9][10][11]. In particular, it has been found that the insertion of an optimized AlN interlayer reduces the alloy related interface roughness and improves therefore the electron mobility dramatically as shown in Fig.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…On the other hand, InN can only be grown at low temperatures and high ammonia partial pressures, whereby high ammonia partial pressures have also a strong effect on the AlN growth rate. However, these problems have been widely overcome in first promising experiments [8][9][10][11]. In particular, it has been found that the insertion of an optimized AlN interlayer reduces the alloy related interface roughness and improves therefore the electron mobility dramatically as shown in Fig.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…5,6 Recently, the insertion of a thin ͑ϳ1 ML͒ film of AlN in the HEMT structure has been shown to improve the device performance by increasing the two dimensional electron gas ͑2DEG͒ confinement and reducing alloy scattering. [7][8][9] However, much less work has been done on AlN/GaN heterostructure for HEMT devices mainly due to the difficulty in growing high-quality AlN barrier layers on GaN by either metal organic chemical vapor deposition 10 ͑MOCVD͒ or molecular beam epitaxy ͑MBE͒. [11][12][13] Nonetheless, the expected reduction in short channel effects and lower threshold voltages, using ultrathin AlN barrier layers, makes these structures of great interest for very high frequency and high power applications.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Despite their potential applications in electronic and optical devices, the fabrication of high quality lattice-matched InAlN epitaxial layers on GaN remains challenging task irrespective of employing sophisticated epitaxial deposition methods such as molecular beam epitaxy (MBE) and metal-organic chemical vapor deposition (MOCVD). The spinodal phase separation and composition inhomogeneity due to the large thermodynamic miscibility gap caused by the large difference of covalent bond length between AlN and InN makes it difficult in alloying at optimum growth temperature.…”
Section: Introductionmentioning
confidence: 99%